Making Summer Count How Summer Programs Can Boost Children's Learning - McCombs, Jennifer Sloan (RAND Corporation, 2011)
Research has shown that students' skills and knowledge often deteriorate during the summer months, with low-income students facing the largest losses. School districts and summer programming providers can benefit from the lessons learned by other programs in terms of developing strategies to maximize program effectiveness and quality, student participation, and strategic partnerships and funding.